Open Universities: Old Concepts and Contemporary Challenges - Daniel, John S. (International Review of Research in Open and Distributed Learning, 2019)
We begin by summarising Prasad’s (2018) work on the disconnect between the social purposes of open universities and their achievement. Next, we will revisit the concept of the iron triangle from the 1990s, which explores the three topics access, cost, and quality. How does it apply to distance education conducted with today’s technologies? A distinction made in the 1970s between independent and interactive learning activities helps us pursue this question further. A discussion among open university executive heads from around the world in 2017 sets the stage for the final section, which reflects on the current challenges facing open universities. How should they address the competition from the rapidly expanding online offerings of campus institutions? We review economic models, the use of technology, governance and management arrangements, and teaching. The successful systems conceived by the UK Open University in the late 1960s stimulated the creation of many other open universities. How should they be updated today?